2015
DOI: 10.1002/hipo.22443
|View full text |Cite
|
Sign up to set email alerts
|

Navigating life

Abstract: The discoveries of “place cells” in the hippocampus and “grid cells” in the entorhinal cortex are landmark achievements in relating behavior to neural activity, permitting analysis of a powerful system for spatial representation in the brain. The contributions of this work include not only the empirical findings but also the approach this work pioneered of examining neural activity in complex behaviors with real ecological validity in freely moving animals, and of attempting to place the findings in the larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 66 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…We also applied ASAT-10 corrected volumes to the investigation of how hippocampal structure might support cognition in early development. While the importance of the hippocampus in supporting memory and spatial navigation in adults and children is well recognized [Burgess et al, 2002;Ghetti and Lee, 2011], the hippocampus is hypothesized to act in the service of other forms of cognition including certain aspects of language [Cohen, 2015;Duff and Brown-Schmidt, 2012]. [TQ1]In adults, hippocampal activation has been associated with learning novel vocabulary [Breitenstein et al, 2005;Jung et al, 2014].…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We also applied ASAT-10 corrected volumes to the investigation of how hippocampal structure might support cognition in early development. While the importance of the hippocampus in supporting memory and spatial navigation in adults and children is well recognized [Burgess et al, 2002;Ghetti and Lee, 2011], the hippocampus is hypothesized to act in the service of other forms of cognition including certain aspects of language [Cohen, 2015;Duff and Brown-Schmidt, 2012]. [TQ1]In adults, hippocampal activation has been associated with learning novel vocabulary [Breitenstein et al, 2005;Jung et al, 2014].…”
Section: Studymentioning
confidence: 99%
“…Data from the adult literature have documented relations between language and hippocampal structure and function [e.g. Cohen, 2015;Duff and Brown-Schmidt, 2012). Initial evidence using voxel-based morphometry in infants [Deniz Can et al, 2013] suggested these relations also exist between early language development and hippocampal structure in infancy.…”
Section: Figurementioning
confidence: 99%
“…As we interact with the world, we are constantly encoding information, updating mental representations, and altering our behavior to meet changing situational demands; this is an essential part of the human experience integrally tied to memory (Moscovitch, Cabeza, Winocur, & Nadel, 2016;Cohen, 2015;Eichenbaum & Cohen, 2014;Maguire & Mullally, 2013). Such behaviors are often context dependent; for example, remembering that to visit your friend at work, you need to go to her third-floor office, but to visit her at home, you need to go to her first-floor apartment.…”
Section: Introductionmentioning
confidence: 99%
“…Relational memory is a critical component of higher-order cognitive functioning (Konkel et al, 2008;Moscovitch, 2008;Addis et al, 2011;Duff and Brown-Schmidt, 2012;Cohen, 2015) and is sensitive to neurological disturbances and aging (Ryan et al, 2013;D'Angelo et al, in press). Relational memory impairments can lead to impairments in the ability to infer novel information indirectly from prior learning (Smith and Squire, 2005;Ryan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%